2021
DOI: 10.1111/1751-2980.12973
|View full text |Cite
|
Sign up to set email alerts
|

The etiology of achalasia: An immune‐dominant disease

Abstract: There is accumulating evidence suggesting that an autoimmune component is involved in esophageal achalasia. An increase in immune cells, cytokines, chemokines, and autoimmune antibodies in serum and infiltration of immune cells in tissues support the view that immune-mediated inflammation is a crucial pathogenesis of inhibitory neuron degeneration in the lower esophageal sphincter. Infection of viruses such as the herpes virus family has been suspected of provoking the autoimmune reaction. Meanwhile, previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 89 publications
1
14
0
1
Order By: Relevance
“…Given that neural degeneration in the esophageal myenteric plexus, 12 some have postulated that an upstream viral insult coupled with an aberrant immune system response may be responsible for causing this damage 13,14 . This connection implicates infectious and autoimmune diseases as potential drivers of achalasia pathogenesis 15‐17 . Existing studies examining the association between these diseases with achalasia have demonstrated a positive relationship, though they are limited by small sample sizes and control selection that is not directly sampled from the underlying source population that gave rise to the cases 18,19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that neural degeneration in the esophageal myenteric plexus, 12 some have postulated that an upstream viral insult coupled with an aberrant immune system response may be responsible for causing this damage 13,14 . This connection implicates infectious and autoimmune diseases as potential drivers of achalasia pathogenesis 15‐17 . Existing studies examining the association between these diseases with achalasia have demonstrated a positive relationship, though they are limited by small sample sizes and control selection that is not directly sampled from the underlying source population that gave rise to the cases 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 This connection implicates infectious and autoimmune diseases as potential drivers of achalasia pathogenesis. [15][16][17] Existing studies examining the association between these diseases with achalasia have demonstrated a positive relationship, though they are limited by small sample sizes and control selection that is not directly sampled from the underlying source population that gave rise to the cases. 18,19 Such designs have high risk of bias.…”
mentioning
confidence: 99%
“…Interestingly, a possible association between achalasia, the destruction of myenteric neurons and viral infection has been proposed, indicating a possible association between achalasia and viral infection. Potential viruses associated with achalasia include herpes simplex virus (HSV)-1, varicella-zoster virus (VZV), measles, mumps, and human immunodeficiency virus (HIV) 32 . Among the up-regulated genes associated to viral response was IFNε , a unique member of the type I interferon family which plays crucial role in innate and adaptive responses to viral infection 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, other studies have addressed the emerging role of proinflammatory cytokines (interleukin (IL)-22, IL-17, interferon-gamma, IL-6, and tumor necrosis factor alpha) that were overexpressed in achalasia patients compared with controls [23,25]. However, still more studies are needed to explore the dominant immune cells and cytokines that trigger the development of achalasia and to determine the underlying trigger for the activation of those immune cells and pathways [26]. Still, an underlying viral infection is an acknowledged and reported factor behind achalasia development [27,28].…”
Section: Etiologymentioning
confidence: 99%